Reconstruction of the Base of Skull Defect—Lessons Learned over 25 Combined Years - Rowe, Dan; Emmett, James (Journal of Neurological Surgery Part B: Skull Base, 2016)
With an increased understanding of the pathological processes involved in perinerual spread, surgery has come to play a greater role in its management. As skull base techniques have been refined, the reconstructive surgeon has been presented with increasingly complex and voluminous defects requiring repair. To enable such surgery to have acceptable outcomes, attention to form and function is paramount. This article describes the methods of repair, which have evolved over the last 25 years of practice, and that we find to be both reliable and durable. Our accumulated experience is presented as a treatment algorithm, which will aid the skull base reconstructive surgeon to achieve success for the wide variety of defects encountered with these patients.
Keywords: skull base defect; perineural spread; skull base malignancy; free flap reconstruction; cerebrospinal fluid leak